Hey there :)
![\frac{7}{2}, \frac{9}{4},1, -\frac{1}{4} , -\frac{3}{2} , \frac{?}{?}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B2%7D%2C%20%20%5Cfrac%7B9%7D%7B4%7D%2C1%2C%20-%5Cfrac%7B1%7D%7B4%7D%20%2C%20-%5Cfrac%7B3%7D%7B2%7D%20%2C%20%20%5Cfrac%7B%3F%7D%7B%3F%7D%20)
We can find the common difference here as it is an arithmetic sequence.
The common difference between each term is:
![\frac{5}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B5%7D%7B4%7D%20)
![\frac{7}{2} - \frac{5}{4} = \frac{9}{4}](https://tex.z-dn.net/?f=%20%5Cfrac%7B7%7D%7B2%7D%20-%20%5Cfrac%7B5%7D%7B4%7D%20%3D%20%5Cfrac%7B9%7D%7B4%7D%20)
We can find the unknown term by:
![-\frac{3}{2}- \frac{5}{4}= -\frac{11}{4}](https://tex.z-dn.net/?f=%20-%5Cfrac%7B3%7D%7B2%7D-%20%5Cfrac%7B5%7D%7B4%7D%3D%20-%5Cfrac%7B11%7D%7B4%7D%20%20%20)
{easier way in this example}
OR
by the formula for finding the nth term
a₆ =
{a₆ because it is the 6th term to be found, (6-1) the nth term minus 1}
a₆ =
![- \frac{11}{4}](https://tex.z-dn.net/?f=-%20%5Cfrac%7B11%7D%7B4%7D%20)
However this way is not essential here as the previous term is given.